Scaffolding Remote Learning: A Phenomenological Study of Parents’ Expe-riences in Times of Pandemic - Develos, Jicyl A.; Garcia, Merlie D.; Torrefranca, Jasmyne C.; Molanda, Ma. Carissa (Future Science / FSH-PH Publications, 2023)
COVID-19 poses significant risks to global education. It has shifted traditional learning in the classroom to remote learning at home. The Department of Education initiated a continuity plan in the Philippines that applies a remote learning approach. In remote learning, parents became active participants by being solid scaffolds for their children's learning at home. Through a phenomenological design, the study explored the lived experiences of parents during the pandemic times. The data was gathered through one-on-one interviews with each of the six parent participants, with strict observance of basic IATF protocols like mask-wearing and social distancing. The collected responses were transcribed, examined, coded, and broken down into themes. After data analysis, three significant themes emerged: the description of parents' experiences in scaffolding their children's remote learning, the help extended by the parents to minimize academic stress, and the effects of remote learning on their children's education. The analyzed data revealed that parents became successful scaffolders amid the struggles and lack thereof. Furthermore, parents realized that, while remote learning may not be the best option for their children due to demotivation in learning, it is one way to keep their children safe while learning. Based on the findings, significant measures may be adopted by the Department of Education, teachers, parents, and future researchers, particularly in enhancing modules and learning environments that are more learner-centered.